PENGARUH LOYALITAS ANGGOTA TERHADAP PELAYANAN KOPERASI JASA “MEKAR KARYA BERSAMA” PT. PLN KUBU RAYA - Kurniawati Kurniawati; Aminuyati Aminuyati; Bambang Genjik (Universitas Tanjungpura, 2019)
AbstractThe purpose of this research was to know the influence of loyalty of members to the service cooperative of “Mekar Karya Bersama” PT. PLN (Persero) Wilayah Kalimantan Barat Kubu Raya. The research method used is descriptive with the form of research is relationship study. The population in this research were 324 members. The number of samples in this reasearch were 77 members. this research used the simple random sampling technique. Data collection techniques in this reasearch were direct communication techniques (interview guidelines), indirect communication techniques (questionnaire), and documentary techniques (data of RAT). the result of this research showed that the percentage of the member loyalty variable is 80.33% in the high category and the Cooperative service variable percentage is 83.94% in the high category. The results of the reserch showed that there is an influence of member loyalty on Cooperative services which is indicated by the significance of the count of 0,000<0,05 and the value of t count>t table that is 6,170>1,992. And then the coefficient of determination in this research is amounted for 33.7% while the rest 66.3% is influenced by independent variables not examined in this research, such as employee ability, work motivation, organizational structure and service system.Keywords: Cooperative Service, Loyalty of Members